Congenital scrub typhus: a case report and literature review - Liang, Pinghua; Su, Zengling; Chen, Min; Li, Sitao (Frontiers in Pediatrics, 2023)
Background This study aimed to analyze the clinical course of a newborn with congenital scrub typhus caused by vertical transmission and explore early diagnosis and treatment strategies. The clinical data of the neonate was retrospectively analyzed, and the related literature was reviewed.The newborn was a full-term one, with a good Apgar score at birth. The neonate had apnea at 3 hours of life requiring NICU care and iv antibiotics (piperacillin) for suspected sepsis.On examination, there was hepatosplenomegaly. Blood tests revealed anemia and thrombocytopenia and a chest X ray showed patchy inflammation. On day of life 2, he developed fever. In view of worsening on 3 days of life, he required mechanical ventilation, when he presented with dyspnea, hypotension, sensorium depressed and other signs of sepsis. Importantly, the neonate's mother had a history of scrub typhus at 31 + weeks of gestation. While blood culture result was still pending, highthroughput sequencing of blood and cerebrospinal fluid was performed. To address the suspected scrub typhus infection, oral azithromycin dry suspension was added to the treatment regimen. Highthroughput sequencing results on day of life 5 confirmed a significant presence of 16SrRNA sequences in the blood, suggesting an Orientia tsutsugamushi infection. The neonate steadily recovered and was discharged 16 days after hospitalization. The neonate was followed up for 9 months, and the outcome was favorable, with normal growth and development.Conclusions This article reports a case of congenital Orientia tsutsugamushi infection, a rare condition caused by vertical transmission. Our review of the literature, combined with the presented case, brings the total number of documented congenital scrub typhus cases caused by vertical transmission to eight. Regrettably, one patient from this group unexpectedly died on the 10th day of hospitalization, resulting in a mortality rate of 12.5% (1/8). The special transmission mode and clinical manifestations of this disease alert doctors for timely diagnosis and treatment. Due to the non-specific clinical manifestations of congenital scrub typhus, limited understanding, low index of suspicion among clinicians, and lack of diagnostic facilities, scrub typhus is seriously underdiagnosed in pregnant women, fetuses, and neonates.